The proposed planning method as a parallel element to a real service system for dynamic sharing of service lines. (July 2015) - Klampfer, Saša; Chowdhury, Amor
Abstract: This paper presents a solution to the bottleneck problem with dynamic sharing or leasing of service capacities. From this perspective the use of the proposed method as a parallel element in service capacities sharing is very important, because it enables minimization of the number of interfaces, and consequently of the number of leased lines, with a combination of two service systems with time-opposite peak loads. In this paper we present a new approach, methodology, models and algorithms which solve the problems of dynamic leasing and sharing of service capacities. Highlights: New developed method for planning serving resources. Developed new and flexible models for planning resources and advanced sharing of service lines. Adaptive in-time control. Adaptive predicting. Developed experimental tool with modular structure.